Optical power limitations in spectral-amplitude- coding optical code-division multiple-access systems due to stimulated Raman scattering - Al-Qazwini, Zaineb A. T.; Abdullah, Mohamad Khazani; Mokhtar, Makhfudzah (IEEE, 2008)
In is paper, the maximum power per chip to keep the Stimulated Raman Scattering (SRS)- induced tilt below a specific level in Spectral-Amplitude-Coding Optical Code-Division Multiple-Access (SAC-OCDMA) is evaluated for different number of users. A number of computer simulations have been conducted for this purpose. It is shown that as number of users grows, the power per chip must be decreased to control the SRS-induced tilt and to keep it below acceptable levels. It is also shown that SRS-induced tilt can significantly limit the power per chip levels when the number of users is large. This is the first time such a study is reported for OCDMA systems.